III Doroczne Spotkania "Debiuty poetyckie-73" : Warszawa 27 stycznia 1974. / W. Markiewicz. - Markiewicz, W. (grafik) (RSW "Prasa-Książka-Ruch", 1974)
Plakat imprezy, pegaz z biało-czerwonym skrzydłami.